THE EFFECTIVENESS OF COOPERATION BETWEEN YOGYAKARTA AND VICTORIA THROUGH YOUNG MUSICIAN PROGRAM - yoga arif kurniawan (Mediasi: Journal of International Relations, 2018)
Indonesia and Australia are unique neighbors where they have some differences in terms of geographical, linguistic, religious, and racial. Having striking differences, they often leads to misperception which ultimately affects the ups and downs of bilateral relations between the two countries. Young Musician Program as a mean of cultural exchange of Indonesia and Australia has several functions. The implementation of diplomacy through culture is as an effort to improve the image of the nation abroad to achieve the national interest. On the other hand, cross-cultural communication is essential to achieving mutual understanding and mutually beneficial cooperation and building harmonious international relations. Based on Islamic diplomacy, cooperation between countries is carried out by prioritizing equality, equity, and justice in order to minimize the occurrence of conflict. Yogyakarta as one of the cities in Indonesia with great cultural potential needs to be developed better,so it can support the diplomacy process to achieve national interest.Keywords: Young Musician Program, Culture, Cooperation.